Cavitation bubble- and gas bubble-induced fractional precipitation of paclitaxel from Taxus chinensis. (December 2020) - Kang, Hoe-Jong; Kim, Jin-Hyun
Graphical abstract: Highlights: A novel fractional precipitation of paclitaxel was developed. Higher precipitation rate was found with bubble induced solutions. Precipitation time was dramatically shortened. The precipitation mechanism was established. Abstract: In this study, a fractional precipitation technique of paclitaxel using ultrasonic cavitation bubbles and gas bubbles is presented. Precipitation efficiency has been dramatically improved, and the time required for precipitation has been reduced by 20–30 times compared to conventional methods. As a result of investigating the mechanism of fractional precipitation in which cavitation and gas bubbles were introduced, it was found that the bubble surface itself acts as a nucleation site, resulting in faster nucleation and thereby improving precipitation efficiency. In addition, compared to the conventional fractional precipitation, the particle size was reduced by 7.8–8.9 times and 4.7–4.9 times for cavitation bubbles and gas bubbles, respectively, and the diffusion coefficient was increased by 10.3–11.9 times (cavitation bubble) and 4.7–4.9 times (gas bubble).